Football boot insoles and sensitivity to extent of ankle inversion movement. Issue 2 (1st April 2003) - Waddington, G; Adams, R
Abstract : Background: The capacity of the plantar sole of the foot to convey information about foot position is reduced by conventional smooth boot insoles, compared with barefoot surface contact. Objective: To test the hypothesis that movement discrimination may be restored by inserting textured replacement insoles, achieved by changing footwear conditions and measuring the accuracy of judgments of the extent of ankle inversion movement. Methods: An automated testing device, the ankle movement extent discrimination apparatus (AMEDA), developed to assess active ankle function in weight bearing without a balance demand, was used to test the effects of sole inserts in soccer boots. Seventeen elite soccer players, the members of the 2000 Australian Women's soccer squad (34 ankles), took part in the study. Subjects were randomly allocated to start testing in: bare feet, their own football boots, own football boot and replacement insole, and on the left or right side. Subjects underwent six 50 trial blocks, in which they completed all footwear conditions. The sole inserts were cut to size for each foot from textured rubber "finger profile" sheeting. Results: Movement discrimination scores were significantly worse when subjects wore their football boots and socks, compared with barefoot data collected at the same time. The substitution of textured insoles for conventional smooth insoles in the football boots was found to restore movement discrimination to barefoot levels. Conclusions: The lower active movement discrimination scores of athletes when wearing football boots with smooth insoles suggest that the insole is one aspect of football boot and sport shoe design that could be modified to provide the sensory feedback needed for accurate foot positioning.